Low self-esteem in adolescents with sickle cell disease: Determinants and coping mechanisms; A mixed methods study - Janipher Nakabuye; Wani Muzeyi; Annet Nakirulu; Sarah Kiguli; Grace Ndeezi; Deogratias Munube (PLoS ONE, 2026)
Background Sickle Cell Disease (SCD) is a chronic genetic condition affecting approximately 112 per 100,000 live births globally, with adolescents being particularly vulnerable. Beyond its physical burden, SCD can significantly impact adolescents’ mental health, particularly self-esteem. While positive coping strategies can mitigate these effects, data on self-esteem among adolescents with SCD in Uganda remain limited. The objective of this study was to determine the prevalence, associated factors, and coping mechanisms of low self-esteem among adolescents with SCD attending the Sickle Cell Clinic (SCC) at Mulago National Referral Hospital (MNRH). Methods A sequential explanatory mixed-methods study was conducted at the SCC of MNRH from January to March 2024. Quantitative data were collected from 356 adolescents. Low self-esteem was defined as a total Rosenberg self-esteem score of less than 15. For analysis of factors associated with low self-esteem, modified Poisson regression with a log link and robust standard errors was used to estimate prevalence ratios (PRs) and their 95% CIs. Qualitative data on coping mechanisms were obtained through in-depth interviews with nine adolescents and three key informant interviews with health workers. Thematic analysis was done guided by the THRIVE framework. Results The prevalence of low self-esteem was 21.6% (95% CI: 17.6–26.3%). Lower prevalence of low self-esteem was observed among adolescents not frequently absent from school (aPR = 0.94, 95% CI 0.90–0.99, P = 0.011) and those without limitations to physical activity (aPR = 0.94, 95% CI 0.90–0.98, P = 0.005), while limited social engagement was associated with higher prevalence (aPR = 1.16, 95% CI 1.03–1.31, P = 0.014).”Coping mechanisms reported by adolescents included adherence to medication, healthy eating and hydration, participation in social activities and hobbies, prayer, and peer awareness. Conclusion Adolescents with SCD are at considerable risk of low self-esteem, particularly those with limited physical activity, social involvement, and frequent school absenteeism. Interventions promoting healthy lifestyles, consistent medication use, peer support, and social engagement may help strengthen self-esteem in this population.